A Civic Budget as a form of civil participation, or an institutional PR tool. The Civic Budget in the City of Poznań - Ossowski, Szymon (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The paper discusses the Civic Budget of the City of Poznań (CBP). The analysis focuses on the nature of the CBP and the extent to which it is a participatory budget or rather a PR instrument. The hypothesis is proposed that participatory budgets in Poland are more of a PR instrument than participatory budgets in the strict sense. In order to verify this hypothesis the example of Poznań is analyzed, including the evaluation report of the CBP16. It is concluded that such civic budgets as the CBP can hardly be described as participatory budgets in the strict sense. They do not involve enough consultation, deliberation or actual co-deciding. Too few people are involved in the idea of civic budgets and a clear majority of those who do, only take part in the vote. There are only a few people involved on a long-term basis. All this makes the CBP more of a contest and plebiscite, rather than a participatory budget, which is confirmed by the comparison of the principles and practice of the CBP with the definitions of participatory budgets.

W artykule omówiono instytucję Poznańskiego Budżetu Obywatelskiego. Przeprowadzona analiza dotyczy istoty PBO – ile w nim z budżetów partycypacyjnych a ile z public relations. Postawiona hipoteza uznaje polskie budżety partycypacyjne w większym stopniu za narzędzie PR niż budżet partycypacyjny sensu stricto. Weryfikując hipotezę posłużono się przykładem poznańskim, w tym raportem z ewaluacji PBO16. W efekcie należy stwierdzić, że budżety obywatelskie takie jak PBO trudno zaliczyć do budżetów partycypacyjnych sensu stricto. Za mało w nich konsultacji, deliberacji, faktycznego współdecydowania. Za mało ludzi angażuje się w tę ideę, a jeśli już to zdecydowana większość tylko podczas głosowania. Osób dłużej działających jest niewielu. Dlatego też PBO to w większym stopniu konkurs, rodzaj plebiscytu, niż budżet partycypacyjny, jeżeli zestawimy zasady i praktykę PBO z definicjami budżetów partycypacyjnych.
Budżet obywatelski jako forma partycypacji mieszkańców czy narzędzie PR urzędu? Przykład Poznańskiego Budżetu Obywatelskiego
Keywords: participatory budget; budżet partycypacyjny; Civic Budget of the City of Poznań (CBP); Poznański Budżet Obywatelski; public relations of local governments; samorządowe public relations; city promotion; promocja miast